Feasibility of continuous high-resolution bioreactance monitoring during cesarean delivery under spinal anesthesia - Gaik, Christine; Bahle, Tabea; Keil, Corinna; Wulf, Hinnerk; Vojnar, Benjamin (Frontiers in Medicine, 2025)
PurposeThis study is the first to apply bioreactance-based hemodynamic monitoring with a 4-s interval during cesarean delivery under spinal anesthesia. We evaluated the feasibility of continuous, high-resolution perioperative monitoring in a routine clinical setting, with a particular focus on the temporal relationship between hypotension and changes in advanced hemodynamic parameters.MethodsThis prospective observational study conducted between December 2023 and April 2024 included 51 healthy parturients scheduled for elective cesarean delivery under spinal anesthesia were included. All participants underwent continuous non-invasive hemodynamic monitoring using bioreactance technology. Hemodynamic parameters were recorded at 4-s intervals. The primary outcome was the relative change in the stroke volume index (SVI) from baseline. The secondary endpoints included signal quality, data integrity, and trends in hemodynamic parameters.ResultsA reduction in the stroke volume index (SVI) of ≥20% was observed in 29 of 51 patients. The median percentage change in SVI from baseline was −18.9% [IQR − 31.5 to −6.1]; p < 0.001. The median time from the onset of relevant SVI decline to the occurrence of hypotension was 2:20 min [IQR 1:16–3:56]. The total cumulative observation time for all patients was 3,781 min. At a 4-s sampling interval, approximately 56,713 data points per hemodynamic parameter were expected. The signal loss was minimal, with less than 0.5% missing data per parameter.ConclusionThis method proved to be feasible and yielded stable, high-resolution hemodynamic data. Among all parameters, SVI showed the most consistent baseline values prior to anesthesia. It also demonstrated the most pronounced change, with a statistically significant decline in the majority of subjects between spinal anesthesia and the onset of first hypotension. In such cases, the marked decline in SVI may serve as an early indicator of impending hemodynamic compromise. These results from a low-risk obstetric cohort may inform future research on high-risk populations.